Implementasi Wisata Berkelanjutan Melalui Kegiatan Wisata Edukasi Bahari di Mangrove Bintan Lestari, Kabupaten Bintan - Andesta, Indah (Politeknik Bosowa, 2025)
Mangrove Bintan Lestari is a tourism awareness group in Sebong Pereh Village, Bintan Regency, Riau Islands. Mangrove Bintan Lestari is a form of tourism in Bintan Regency that highlights marine edu tourism in mangroves. The concept taken is sustainable tourism through practices carried out by Mangrove Bintan Lestari. In this study, the highlighted is marine edu tourism activities in Mangrove Bintan Lestari in line with the concept of sustainable tourism. Qualitative descriptive research by describing tourist activities or attractions at Mangrove Bintan Lestari through data collection techniques such as interviews, observations, and literature reviews. Mangrove Bintan Lestari implements mangrove nurseries, mangrove planting, training, and educational tourism activities. Mangrove Bintan Lestari continues to experience development both in the field of cooperation or from activities that are tourist attractions in Mangrove Bintan Lestari. Activities began in 2019 by continuing to make the main activities educational tourism for mangrove planting and mangrove nurseries. In 2024, activities developed such as mangrove eco-print and local culture of the local community. Mangrove Bintan Lestari, involves the community in tourism activities such as in the preparation stage for mangrove nurseries and planting, in tourism activities such as the community participating in mangrove planting, mangrove eco-print activities. In addition, the community is involved in providing consumption for tourists. This provides additional employment opportunities and economic growth for the local community.